The Prognostic Value and Mechanisms of TMEM16A in Human Cancer - Chen, Wenjian; Gu, Meng; Gao, Chaobing; Chen, Bangjie; Yang, Junfa; Xie, Xiaoli; Wang, Xinyi; Sun, Jun; Wang, Jinian (Frontiers in Molecular Biosciences, 2021)
Transmembrane protein 16A (TMEM16A) is a calcium ion-dependent chloride channel located on the cell membrane. Numerous research results have shown that TMEM16A is abnormally expressed in many cancers. Mechanically, TMEM16A participates in cancer proliferation and migration by affecting the MAPK and CAMK signaling pathways. Additionally, it is well documented that TMEM16A regulates the proliferation of cancer cells by interacting with epithelial growth factor receptor (EGFR) in head and neck squamous cell carcinoma (HNSCC). Meanwhile, as an EGFR activator, TMEM16A is considered as an oncogene or a tumor-promoting factor. More and more experimental data showed that down-regulation of TMEM16A or gene targeted therapy may be an effective treatment for cancer. Here, the study reviewed the results of current studies on the role and potential clinical application of TMEM16A in various cancers. Finally, we discussed the potential of TMEM16A as a latent new target in cancer treatment and cancer diagnosis biomarker.